LUNG CANCER: EPIDEMIOLOGY AND TREATMENT PARADIGMS IN A SINGLE CENTER FROM PAKISTAN - BANO , K; ZAFAR , A; NADEEM , R; SHEIKH , F; KHAN , RMFUR; NAWAZ , MJ (Biological and Clinical Sciences Research Journal, 2023)
Lung cancer is the second most common cancer worldwide and the leading cancer in men, with women following closely behind as the second most affected group. In 2020, there were more than 2.2 million new reported cases of lung cancer. According to Globocan, it is the third most common cancer in Pakistan, with an incidence rate of 5.9% in 2018 and a mortality rate of 7.8%. This study aims to explore the epidemiology, risk factors, and outcomes associated with lung cancer in Pakistan. The study is a retrospective observational investigation conducted at Jinnah Hospital in Lahore. The data of 50 adult patients who were diagnosed with biopsy-proven lung carcinoma, aged 20 years or older, and had received at least four cycles of first-line therapy were collected from their files. Patients were enrolled at random, regardless of gender. The results showed that 80% of the patients were male, while only 20% were female. The majority of the patients, 58%, had a history of smoking, with males accounting for 50% of this group. At presentation, 78% of the patients had stage 4 disease, and 68% received platinum with paclitaxel upfront. Forty-eight percent of the patients were above 60 years of age. Squamous cell and adenocarcinoma lung were the most common types of lung cancer, accounting for 34% and 30% of cases, respectively. After four cycles of first-line therapy, 30% of patients showed a partial response, while 56% continued with second-line treatment. In conclusion, lung cancer is a significant health concern in Pakistan, and measures are needed to decrease its incidence. Further studies with larger sample sizes are required to understand better the prevalence and effectiveness of treatment paradigms for lung cancer in Pakistan.